BIAYA KONSTRUKSI DAN VOLUME KAYU PADA JALAN REL KAYU DAN REL BESI - Dulsalam Dulsalam; Apul Sianturi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
An investigation on construction cost and wood use in railroad tracks in swamp forests has been carried out at two companies located in West Kalimantan in 1983.The investigation arrives at the following conclusion:The construction of both wooden and steel railroad tracks uses 4 layers of sleepers. The difference between the two lies in the rails itself.The bearing capacity of steel railroad track ranges from 2 to 4 tons, while that of wooden railroad track from 10 to 15 tons.Construction cost of wooden railroad tracks is lower than that of steel railroad tracks, i.e., Rp. 2.350.000.-/km and Rp. 11.483.000.-/km respectively. The volume of wood used in wooden and steel railroad tracks is 243 m3/km and 241 m3/km respectively.The amounts of wood used between wooden railroad tracks and steel railroad tracks do not differ significantly. Among layer, however, they differ highly significantly.